Methodological aspects around the reconstruction of surname sub-sets in bimodal networks - Fernández, Federico (AWARI, 2020)
This article addresses the methodological aspects surrounding the transformation of a cadastral land registry from the end of the 19th century belonging to the department of Humahuacua, Jujuy province (Argentina), in a series of bimodal matrices and networks. The idea that has guided the relational treatment of the data towards said historical sources, starts from the premise that certain individuals carrying a discrete set of surnames, and who have shared similar monetary amounts of appraisal declared in the said land cadastre, were more likely to link with each other in different areas of social life, such as the limited political and regional power circle of the late nineteenth century in Jujuy. The results obtained show the possibility of delimiting and reconstructing sub-sets of surnames that are linked less and/or more frequently to each other, according to four pre-constructed appraisal categories based on a segmentation of the registered monetary valuations in the land registry. Likewise, and as a product of this new grouping of information arising from the application of Social Network Analysis (ARS), it is feasible to limit the study to the qualitative aspects (age, residence, descent, nuptial ties, baptismal sponsorships) of individuals that formed part of these resulting sub-sets, through the focused search of ecclesiastical acts recorded within the same historical period.